The Influence of Geogebra Media on the Ability to Understand Class XI Concepts in Three-Dimensional Materials - Adi Sinaga; Eblita Rosa Br Depari; Faradhiya Khairani; Gita Novela Hutapea; Maryana Marpaung; Nidia Lestari; Pera Manurung (Peneliti.net, 2026)
This study examines the effect of GeoGebra learning media on 11th-grade students' understanding of three-dimensional mathematical concepts, specifically cubes. A Pre-Experimental One-Group Pretest-Posttest design was conducted at SMA Negeri 2 Medan. Data collected through pretest and posttest were analyzed using the Wilcoxon Signed Rank Test. The results showed a significant improvement in students' average scores (from 44.38 to 84.10, p < 0.001). Therefore, it can be concluded that GeoGebra's visual and interactive features significantly enhance students' understanding of abstract geometric concepts.